INTERNAL COMMUNICATION STRATEGY OF LEADERS WITHOUT A PUBLIC RELATIONS FUNCTION AT THE DOLOK ILIR TENERA MACHINE FACTORY - Dian Permatasari; Muhammad Husni Ritonga (Journal Analytica Islamica, 2026)
This study aims to analyze the internal communication strategy of leaders at the Tenera Machine Factory (PMT) Dolok Ilir, a manufacturing organization operating without a formal Public Relations (PR) department. Using a descriptive qualitative approach with a case study, data were collected through in-depth interviews, observation, and documentation. The results show that the unit leader performs a substitution function for PR through a hybrid communication strategy. This strategy integrates the use of WhatsApp Groups as a digital channel for rapid and transparent information dissemination, combined with interpersonal communication through "ngumpul pagi" (morning gathering) activities to provide clarification and build emotional closeness. Although the absence of a PR unit poses challenges in the form of message distortion risks and information overload centered on the leader, the use of informal communication channels and a relay system has proven effective in minimizing these obstacles. This study concludes that the leader's interpersonal communication competence and the optimization of instant media are key to the effectiveness of information flow within a minimalist organizational structure.